Consensus protocols for the diagnosis and management of the hereditary autoinflammatory syndromes CAPS, TRAPS and MKD/HIDS: a German PRO-KIND initiative - Sandra Hansmann; Elke Lainka; Gerd Horneff; Dirk Holzinger; Nikolaus Rieber; Annette F. Jansson; Angela Rösen-Wolff; Gabi Erbis; Martina Prelog; Juergen Brunner; Susanne M. Benseler; Jasmin B. Kuemmerle-Deschner (BMC, 2020)
Abstract Background Rare autoinflammatory diseases (AIDs) including Cryopyrin-Associated Periodic Syndrome (CAPS), Tumor Necrosis Receptor-Associated Periodic Syndrome (TRAPS) and Mevalonate Kinase Deficiency Syndrome (MKD)/ Hyper-IgD Syndrome (HIDS) are genetically defined and characterized by recurrent fever episodes and inflammatory organ manifestations. Early diagnosis and early start of effective therapies control the inflammation and prevent organ damage. The PRO-KIND initiative of the German Society of Pediatric Rheumatology (GKJR) aims to harmonize the diagnosis and management of children with rheumatic diseases nationally. The task of the PRO-KIND CAPS/TRAPS/MKD/HIDS working group was to develop evidence-based, consensus diagnosis and management protocols including the first AID treat-to-target strategies. Methods The national CAPS/TRAPS/MKD/HIDS expert working group was established, defined its aims and conducted a comprehensive literature review synthesising the recent (2013 to 2018) published evidence including all available recommendations for diagnosis and management. General and disease-specific statements were anchored in the 2015 SHARE recommendations. An iterative expert review process discussed, adapted and refined these statements. Ultimately the GKJR membership vetted the proposed consensus statements, agreement of 80% was mandatory for inclusion. The approved statements were integrated into three disease specific consensus treatment plans (CTPs). These were developed to enable the implementation of evidence-based, standardized care into clinical practice. Results The CAPS/TRAPS/MKD/HIDS expert working group of 12 German and Austrian paediatric rheumatologists completed the evidence synthesis and modified a total of 38 statements based on the SHARE recommendation framework. In iterative reviews 36 reached the mandatory agreement threshold of 80% in the final GKJR member survey. These included 9 overarching principles and 27 disease-specific statements (7 for CAPS, 11 TRAPS, 9 MKD/HIDS). A diagnostic algorithm was established based on the synthesized evidence. Statements were integrated into diagnosis- and disease activity specific treat-to-target CTPs for CAPS, TRAPS and MKD/HIDS. Conclusions The PRO-KIND CAPS/TRAPS/MKD/HIDS working group established the first evidence-based, actionable treat-to-target consensus treatment plans for three rare hereditary autoinflammatory diseases. These provide a path to a rapid evaluation, effective control of disease activity and tailored adjustment of therapies. Their implementation will decrease variation in care and optimize health outcomes for children with AID.